Determinants of Assault on Football League Referees' during Competitions in Nigeria - Danjuma Moudu Momoh Momoh; Toyosi Olaseyo (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
The assault on referees is an act committed by an individual involved in a match such as players, substitutes, coaches, team officials or spectators against a referee that is of a violent or intimidating nature. This study, therefore, investigated the level of assault of referees in Nigeria's Premier Football League. The participants for the study consisted of two hundred and fifty (250) Nigerian Premier League elite referees, footballers, coaches, and spectators. The purposive sampling technique was used for the study to select the respondents. Sampled used for the study was survey research design. A structured questionnaire with validated and reliability value of 0. 75 was used for data collection. The data was analyzed using the inferential statistics of Chi-square (x2) to test the research questions and hypotheses at 0.05 alpha levels. The three hypotheses of officiating, organization of the league and win at all cost tested, were all rejected. Consequently, some recommendations were made based on the findings of the study.